Pelatihan Perhitungan Zakat Pada Masyarakat Desa Botutonuo Kecamatan Kabila Bone Kabupaten Bone Bolango - Zulkifli Bokiu; Niswatin Niswatin; Nilawaty Yusuf (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
This collaborative service has the theme "Zakat Calculation Training for the Botutonuo Community". This collaborative service activity aims to educate the community about zakat. Knowledge of zakat which includes income that must be subject to zakat and training in zakat calculations. The main target of this zakat calculation literacy outreach activity is the community in Botutonou Village. The method for implementing this service activity is lectures and training on zakat calculations. As a result of this activity, the Botutonuo village community gained knowledge about how to calculate zakat and the provisions for agricultural, livestock and other assets that have met the nisab for which zakat is paid according to Islamic provisions.